Tari Payung of Sibolga Coastal: Aesthetic Review - Sitti Rahmah Sibuea; Yusnizar; Raden (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The discussion in this paper is about the aesthetic review of the Sibolga Pesisir Payung Dance as one of the traditional arts in North Sumatra Province. The method in this paper uses a qualitative descriptive method, through an analysis that describes the situation in the field about Payung dance. This study concludes that the dance on the Sibolga Coast has a very touching meaning, and contains its own beauty value for the community, as seen in the presentation of the Tari Payung from the Sibolga Coastal area. The Tari Payung is a traditional dance of the Sibolga Coastal community which is included in the Sikambang art. This dance is always displayed in the traditional Sumando event (night barinai), or when the bride and groom are side by side on the aisle. This makes the Tari Payung unique, because this dance has messages and advice for the bride and groom as a new couple in building a household.